Solution:
Let "e_1 = (1, 0, 0)", "e_2 = (0, 1, 0)", "e_3 = (0, 0, 1)" be the natural basis of "\\R^3". We have "T \\left( e_1 \\right) = e_1", "T \\left( e_2 \\right) = e_3", and "T \\left( e_3 \\right) = e_1 + e_2 - e_3". The matrix of this transformation with respect to the introduced basis is then
"\\begin{pmatrix} 1 & 0 & 1 \\\\ 0 & 0 & 1 \\\\ 0 & 1 & -1 \\end{pmatrix} \\, ."This matrix is non-degenerate (its determinant is equal to -1), therefore, T is invertible. To find the inverse, we observe that "T^{-1} \\left( e_1 \\right) = e_1", "T^{-1} \\left( e_3 \\right) = e_2", and "T^{-1} \\left( e_1 + e_2 - e_3 \\right) = e_3". From the last equation, we have "T^{-1} \\left( e_2 \\right) = e_3 - T^{-1} \\left( e_1 \\right) + T^{-1} \\left( e_3 \\right) = - e_1 + e_2 + e_3". Then, since "\\left( x_1 , x_2 , x_3 \\right) = x_1 e_1 + x_2 e_2 + x_3 e_3", we obtain
"T^{-1} \\left( x_1 , x_2 , x_3 \\right) = T^{-1} \\left( x_1 e_1 + x_2 e_2 + x_3 e_3 \\right) \\\\ {} = x_1 T^{-1} \\left( e_1 \\right) + x_2 T^{-1} \\left( e_2 \\right) + x_3 T^{-1} \\left( e_3 \\right) \\\\ {} = x_1 e_1 + x_2 \\left( - e_1 + e_2 + e_3 \\right) + x_3 e_2 \\\\ {} = \\left( x_1 - x_2 , x_2 + x_3 , x_2 \\right) \\, ."Answer: T is invertible, with the rule "T^{-1} \\left( x_1 , x_2 , x_3 \\right) = \\left( x_1 - x_2 , x_2 + x_3 , x_2 \\right)".
Comments
Leave a comment